Transformasi Digital dalam Administrasi Publik: Studi Komparatif di Indonesia dan Korea Selatan - Ernialdi Ernialdi; Angelina Ramadhani; Murni Murni; Mutia Rahmah Sari; Ulfa Mutiah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
. Digital transformation in public administration has become a strategic agenda in modern bureaucratic reform aimed at improving effectiveness, efficiency, transparency, and the quality of public services. This study aims to analyze the digital transformation of public administration through a comparative study between Indonesia and South Korea, particularly in the implementation of digital government. The research employs a qualitative method with a comparative study approach and is supported by library research through the collection of secondary data from scientific journals, international institutional reports, government policy documents, and relevant previous studies. Data analysis was conducted descriptively and comparatively using the approaches of Digital Era Governance (DEG), Institutional Theory, New Public Management (NPM), and Socio-Technical Systems Theory. The findings indicate that South Korea has successfully developed an integrated digital government through consistent national policies, strong data interoperability, high bureaucratic capacity, adaptive organizational culture, and equitable digital infrastructure development. Meanwhile, Indonesia is still in the transition stage from e-government to digital government and faces various challenges, such as inter-agency system fragmentation, low data interoperability, unequal digital infrastructure, limited civil servant competencies, and bureaucratic resistance to change. This study concludes that the success of digital transformation in public administration is determined more by institutional strength and bureaucratic reform than merely by technology adoption. Therefore, Indonesia needs to position digital transformation as a comprehensive state reform agenda in order to create a modern, responsive, and public service-oriented government.